Studying the relationship between emulsion structure and lipid digestibility for infant milk : a thesis was present in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Food Technology, at Massey University, Palmerston North, New Zealand - Deng, Le (Massey University, 2020)
Milk, whether maternal or formulated, provides the sole source of nutrition to infants in the early stages of life, providing critical micronutrients, support for the immune function and primary dietary macronutrients including lipids. In healthy adults, lipids are primarily digested in the small intestine. However, for infants, the neonatal small intestine is not fully developed after birth, so the gastric environment plays a more significant role in milk fat digestion. Clinical studies have shown that maternal milk fat is digested more efficiently than lipids in infant formulae in infants under infant gastric conditions. Compositional differences, the structure of the oil droplets, and especially the interfacial composition may all play a crucial role in influencing lipid digestibility in the infant's stomach. In this thesis, the simulated gastric digestion of model emulsions and commercial infant formula was studied. The model emulsions comprised either a phospholipid or complexed protein-phospholipid interface while keeping all other facets of emulsion properties equivalent. Gastric digestion of these emulsions was carried out across variable pH conditions using an analogue gastric lipase, alone and in combination with pepsin with findings providing insights into the role of each enzyme and their combined effect on gastric lipolysis. The rate and extent of lipolysis were characterised, along with morphological changes to the structure of the oil droplets. Results showed that gastric lipolysis might be influenced by pH conditions in the gastric environment when lipase was present alone in the simulated gastric fluid. The inclusion of pepsin resulted in significant structural changes when emulsions were stabilised with protein, in terms of droplet aggregation, size and morphology. However, no significant differences in the extent of lipolysis were determined. Thus, while the protein interface of both model and formulated emulsions was not observed to be a barrier for gastric lipolysis. Proteolysis of protein stabilised emulsions may lead to very different structural outcomes during gastric digestion when compared to phospholipid stabilised emulsions. While the research within this thesis demonstrates how the gastric environment influences emulsion structure as a consequence of interfacial composition, any specific relationship between structure and relative rate of gastric lipolysis currently remains undetermined. This research also highlights some of the ongoing challenges in the use of in vitro models to provide mechanistic understanding and interpretation of findings from clinical studies.
All Figures are re-used with the publishers' permission.
Keywords: Digestive enzymes; Emulsions; Lipolysis; Milkfat; Infant formulas; 310106 Enzymes